F FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PENGGUNAAN SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PURWOREJO - Rustam, Kuswadi; Affan, Junaidi; Setya Budi, Surawan (Sekolah Tinggi Ilmu Ekonomi SBI, 2024)
This research aims to test and analyze the influence of employee satisfaction factors at the population and civil registration services on the use of the population administration information system in Purworejo Regency. This type of research is quantitative research using primary data by distributing questionnaires. The sample used was 40 employee respondents who used the population administration information system. The data obtained was processed using SPSS version 22. Data analysis techniques used validity and reliability tests. multiple linear regression test, T test, and F test. The results of this research show that 1) system quality (X1) partially has a significant effect on employee satisfaction with a t test result of 3.481. 2) information quality (X2) partially has a significant effect on employee satisfaction with a t test result of 3.923. 3) service quality (X3) partially has a significant effect on employee satisfaction with a t test result of 3.775. 4) partial use of (X4) has no significant effect on employee satisfaction with a t test result of -1.043. 5) net benefits (X5) partially have no significant effect on employee satisfaction with a t test result of -1.608. For the f test, the significance value for the influence of system quality (X1), information quality (X2), service quality (X3), usage (X4), and net benefits (X₅), simultaneously on Y is 0.000 < 0.05 and the f value count 7,720 > f table 2,650, so it can be concluded that there is an influence of system quality (X1), information quality (X2), service quality (X3), usage (X4), and net benefits (X₅), simultaneously on employee satisfaction Y